2017
DOI: 10.1002/macp.201700448
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelasticity and Dynamics of Confined Polyelectrolyte/Layered Silicate Nanocomposites: The Influence of Intercalation and Exfoliation

Abstract: The influence of different confinement regimes on the linear viscoelastic properties of a polyelectrolyte, the protonated poly‐[(dimethylamino) ethyl methacrylate] (PDMAEMAH), is investigated. PDMAEMAH is reinforced with the layered silicate montmorillonite (MMT). Neat MMT and MMT treated with sulfobetaine and ammonia‐based surfactants (MMT/SB and MMT/NH, respectively) are utilized. Transmission electron microscopy and X‐ray scattering show that MMT and MMT/NH produce intercalated morphology, whereas MMT/SB pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Furthermore, in many reports the clay content greatly exceeds 10%, which is contrary to the basis that rather small concentrations (<5%)) of nanofiller would enhance the physical properties of a polymer matrix . It is suggested that the degree of dispersion, the morphology attained in the nanocomposite (i.e., intercalation vs exfoliation) and the inherent degree of confinement induced by the nanoplatelets are key factors driving the physical properties …”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Furthermore, in many reports the clay content greatly exceeds 10%, which is contrary to the basis that rather small concentrations (<5%)) of nanofiller would enhance the physical properties of a polymer matrix . It is suggested that the degree of dispersion, the morphology attained in the nanocomposite (i.e., intercalation vs exfoliation) and the inherent degree of confinement induced by the nanoplatelets are key factors driving the physical properties …”
Section: Introductionmentioning
confidence: 98%
“…It is believed that the macromolecular nanoconfinement found in intercalated morphologies of polymer–clay nanocomposites, would be largely responsible for the changes of thermomechanical properties . It is known that confinement can induce lowering or increasing of the glass transition temperature, T g , in small molecule glassy materials, in glassy polymers, and in polymer nanocomposites . The influence of confinement has also been evidenced in rheological properties when analyzing ultrathin films of polydimethyl siloxane .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations